2022
DOI: 10.1007/s10603-022-09516-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Energy Cost Labelling for Appliances: Evidence from a Randomised Controlled Trial in Ireland

Abstract: Given the longevity of investments in energy-consuming products (such as household appliances, vehicles, and properties), underinvestment in energy efficiency can have long-lasting negative economic and environmental consequences. Previous research has indicated that underinvestment may be due to imperfect information in relation to the long-term benefits of investing in energy efficiency. This paper presents the results of a cluster randomised controlled trial examining an intervention which aims to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Providing lifetime cost information increases the willingness to pay for energy efficiency, but the EU energy label alone does not increase demand for energy-efficient products under a control condition [3]. A recent study [5] found that providing 10-year energy cost information labels or QR codes did not increase the average energy efficiency of the appliances sold, and customers' engagement with the QR code was extremely low. The study also found that while treatment increased the importance of energy efficiency in decision-making, this did not translate into increased efficiency of purchased products.…”
Section: Research On Energy Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing lifetime cost information increases the willingness to pay for energy efficiency, but the EU energy label alone does not increase demand for energy-efficient products under a control condition [3]. A recent study [5] found that providing 10-year energy cost information labels or QR codes did not increase the average energy efficiency of the appliances sold, and customers' engagement with the QR code was extremely low. The study also found that while treatment increased the importance of energy efficiency in decision-making, this did not translate into increased efficiency of purchased products.…”
Section: Research On Energy Labelsmentioning
confidence: 99%
“…The use of energy labels to inform consumers about the energy and environmental impacts of products was a topic of interest in recent research [3][4][5][6][7]. Several of them examined the effectiveness of energy labels in attracting consumer attention and increasing the sales proportion of energy-efficient appliances, but not for durable and expensive goods, such as housing.…”
Section: Introductionmentioning
confidence: 99%